Fatigue-induced increase in intracortical communication between mid/anterior insular and motor cortex during cycling exercise - Hilty, Lea; Langer, Nicolas; Pascual-Marqui, Roberto; Boutellier, Urs; Lutz, Kai (The European journal of neuroscience, 2011)
In the present study, intracortical communication between mid/anterior insular and motor cortex was investigated during a fatiguing cycling exercise. From 16 healthy male subjects performing a constant‐load test at 60% peak oxygen consumption (VO2peak) until volitional exhaustion, electroencephalography data were analysed during repetitive, artefact‐free periods of 1‐min duration. To quantify fatigue‐induced intracortical communication, mean intra‐hemispheric lagged phase synchronization between mid/anterior insular and motor cortex was calculated: (i) at the beginning of cycling; (ii) at the end of cycling; and (iii) during recovery cycling. Results revealed significantly increased lagged phase synchronization at the end of cycling, which returned to baseline during recovery cycling after subjects’ cessation of exercise. Following previous imaging studies reporting the mid/anterior insular cortex as an essential instance processing a variety of sensory stimuli and signalling forthcoming physiological threat, our results provide further evidence that during a fatiguing exercise this structure might not only integrate and evaluate sensory information from the periphery, but also act in communication with the motor cortex. To the best of our knowledge, this is the first study to empirically demonstrate that muscle fatigue leads to changes in interaction between structures of a brain’s neural network. In the present study, intracortical communication between mid/anterior insular and motor cortex was investigated during a fatiguing cycling exercise. From 16 healthy male subjects performing a constant‐load test at 60% peak oxygen consumption (VO2peak) until volitional exhaustion, electroencephalography data were analysed during repetitive, artefact‐free periods of 1‐min duration.